Factores asociados a la enfermedad diarreica aguda en niños menores de 5 años del centro poblado Km 50- Piura (Perú). 2018 - Lizama Prieto, Sissy Tatiana (2019)
Acute diarrheal diseases (ADD) are a health problem, which generally affects early childhood children. This study aimed to determine the factors associated with acute diarrheal disease in children under 5 years of the Km50-Piura 2018 population center. The study was of cases and controls matched 1: 1, data from clinical records and home interview were collected. to the mothers of the minors. Association was determined by Odds ratio with IC95%. The results obtained were: animals in the dwelling (OR = 7; IC:1.99-24.58), overcrowding (OR = 3.18; IC: 1.15-8.84), housing (OR = 25; IC: 5.05-128.87) and proximity to a critical point of solid waste (OR = 19.28, IC 3.92-94.82); were risk factors associated with acute diarrheal disease. The association with personal and domestic hygiene factors (OR = 2.33 and 3.22 respectively); It was not significant. The exclusive breastfeeding factor was a protective factor (OR = 0.097, IC:0.01-0.82). It was concluded that the factors associated with the EDA as risk were: housing, overcrowding, animals in the home and proximity to a critical point of solid waste. The exclusive breastfeeding protective factor was also associated.